Are stakeholders ready to transform phosphorus use in food systems? A transdisciplinary study in a livestock intensive system. Issue 131 (May 2022) - Martin-Ortega, Julia; Rothwell, Shane A.; Anderson, Aine; Okumah, Murat; Lyon, Christopher; Sherry, Erin; Johnston, Christopher; Withers, Paul J.A.; Doody, Donnacha G.
Abstract: Food systems worldwide are vulnerable to Phosphorus (P) supply disruptions and price fluctuations. Current P use is also highly inefficient, generating large surpluses and pollution. Global food security and aquatic ecosystems are in jeopardy if transformative action is not taken. This paper pivots from earlier (predominantly conceptual) work to develop and analyse a P transdisciplinary scenario process, assessing stakeholders potential for transformative thinking in P use in the food system. Northern Ireland, a highly livestock-intensive system, was used as case study for illustrating such process. The stakeholder engagement takes a normative stance in that it sets the explicit premise that the food system needs to be transformed and asks stakeholders to engage in a dialogue on how that transformation can be achieved. A Substance Flow Analysis of P flows and stocks was employed to construct visions for alternative futures and stimulate stakeholder discussions on system responses. These were analysed for their transformative potential using a triple-loop social learning framework. For the most part, stakeholder responses remained transitional or incremental, rather than being fundamentally transformative. The process did unveil some deeper levers that could be acted upon to move the system further along the spectrum of transformational change (e.g. changes in food markets, creation of new P markets, destocking, new types of land production and radical land use changes), providing clues of what an aspirational system could look like. Replicated and adapted elsewhere, this process can serve as diagnostics of current stakeholders thinking and potential, as well as for the identification of those deeper levers, opening up avenues to work upon for global scale transformation. Highlights: Transdisciplinary process on potential for transformative thinking in P use. Substance Flow Analysis of visions for alternative futures and system responses. Analysed for their transformative potential using triple-loop social learning. Stakeholder responses remained transitional or incremental, not transformative. But some deeper levers that could be acted upon to transform the food system.